Dengue Haemorrhagic Fever with Unusual Presentations and Complications in Sanjiwani General Hospital: A Case Series - Dwi Putri Anjani, I Gusti Agung; I Wayan Eka Saputra (HM Publisher, 2024)
Background: Dengue hemorrhagic fever (DHF) is a viral infection transmitted by Aedes mosquito with a wide clinical spectrum, ranging from mild fever to life-threatening complications. Atypical clinical manifestations of DHF can cause delays in diagnosis and treatment, so it is important to increase clinician awareness of these unusual manifestations. Case presentation: We report four cases of DHF with atypical manifestations: (1) A 50-year-old woman with spontaneous psoas hematoma, (2) An elderly man with pulmonary edema, (3) A young man with acute myocarditis, and (4) A middle-aged man. middle-aged with encephalopathy. Conclusion: Atypical manifestations of DHF can occur at various ages and can involve various organs. It is important for clinicians to consider dengue fever as a differential diagnosis in patients with fever and unusual clinical manifestations, especially in dengue-endemic areas. Early diagnosis and appropriate treatment can improve patient clinical outcomes.